2007
DOI: 10.1111/j.1365-3083.2007.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency and Autoimmunity in 22q11.2 Deletion Syndrome

Abstract: 22q11.2 deletion syndrome is the commonest chromosome deletion syndrome. 22q11.2 deletion may result in variable clinical phenotypes which may differ even between patients with identical deletions. Abnormal pharyngeal arch development results in defects in the development of the parathyroid glands, thymus and conotruncal region of the heart. Defective thymic development is associated with impaired immune function. ‘Complete’ DiGeorge syndrome with total absence of the thymus and a severe T‐cell immunodeficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 73 publications
(99 reference statements)
0
93
0
1
Order By: Relevance
“…An explanation of the autoimmune predisposition in 22q11.2 deletion syndrome might be a reduced level of natural regulatory T-cells (nTreg). 47 These nTregs are important in the maintenance of self-tolerance, that is, suppression of the immune response against self-antigens. In our collected cohort of CHARGE patients, nTreg levels were mentioned in only two patients: one patient had few nTregs (no value was mentioned) 23 and the other patient had higher proportions of nTregs compared with two adult controls.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…An explanation of the autoimmune predisposition in 22q11.2 deletion syndrome might be a reduced level of natural regulatory T-cells (nTreg). 47 These nTregs are important in the maintenance of self-tolerance, that is, suppression of the immune response against self-antigens. In our collected cohort of CHARGE patients, nTreg levels were mentioned in only two patients: one patient had few nTregs (no value was mentioned) 23 and the other patient had higher proportions of nTregs compared with two adult controls.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
“…These self-antigens are important for the deletion of autoreactive T-cells. 61 McLean-Tooke et al 47 suggested that the reduced number of nTregs seen in 22q11.2 deletion syndrome is related to thymic function and structure. So the autoimmune predisposition in 22q11.2 deletion syndrome might be explained by both impaired thymic and T-cell development.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
“…1. Bracket shows the most common area of deletion in 22q11.2 deletion syndrome, with 85% of patients missing the genes in this region (7). A smaller subset of patients is missing a smaller area, which may not include the autoimmunity locus identified.…”
Section: Resultsmentioning
confidence: 99%
“…Autoimmune disease occurs about 10-times more commonly in patients with 22q11.2DS compared with the general population (7,10). Polyarticular juvenile rheumatoid arthritis is estimated to occur up to 150-times more frequently (11), autoimmune cytopenias affect 20-to 200-times more patients (varies by source and type of cytopenia) (12), and autoimmune thyroid disease is found in almost 10% of patients, 1.8% with hyperthyroidism and 7.7% with hypothyroidism (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation